Tratamento conjugado de lixiviado de aterro sanitário e esgoto sanitário em lagoas de estabilização rasas - Campos, Andrezza Raphaella Costa (2012)
The search to develop viable and efficient alternatives for the treatment of landfill leachate, provided the emergence of initiatives to research the combined treatment of landfill leachate and sewage, in order to treat the leachate by diluting it in sewage, reducing the high concentrations of organic matter and ammonia nitrogen, allowing proper proportions to conventional treatment. In this study was analyzed the efficiency of combined treatment of leachate, in nature, and sanitary sewage in a series of shallow stabilization ponds. The experimental system was designed, built and monitored in physical dependencies of the Experimental Station of Biological Treatment of Sewage (EXTRABES), belonging to the State University of Paraiba, Campina Grande - PB, Brazil (7 ° 13'11'' south, 35 ° 52 '31'' west and 550 m above sea level), consisting of four shallow stabilization ponds in series, with a facultative pond, followed by three maturation ponds. Was prepared daily, the required volume of substrate from the mixture of 1% of landfill leachate, in nature, and 99% of sewage, used for feeding the series of stabilization ponds. The average removal efficiency of COD Total, COD Filtered, BOD5 nd N-NH4 + were 49%, 48%, 69% and 86%, respectively. It was further observed that the parameters of pH, BOD , fit the patterns established by CONAMA 430/2011, for disposal of effluent of sewage treatment system in water bodies. Were performed two profiles in the series of stabilization ponds, aiming to better understand the behavior of the experimental system. During the profiles was observed that the parameters of pH, temperature and dissolved oxygen varies during the day, with higher values for the period of greatest insolation, situated between 11 and 14 hours. Based on these results, the combined treatment of landfill leachate and sewage, can be considered as an effective alternative for the treatment of leachate, adapting it to a biological process with low operating costs, and preventing it may cause environmental impacts 5 and N-NH4 +